2021
DOI: 10.1111/cts.13203
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous metabolic markers for predicting the activity of dihydropyrimidine dehydrogenase

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For instance, an increase in endogenous compounds potentially leading to DPD inhibition could be observed in the plasma of patients with renal impairment. 20 , 22 , 23 , 24 Nevertheless, a case of dialyzed patients who tolerated standard 5-FU doses despite high levels uracilemia has been observed, 10 questioning the uracilemia-based phenotype in this situation. In the case of ‘false’ hyperuracilemia, as a pre-therapeutic plasma value of U ≥ 16 ng/ml may lead to a decrease in the 5-FU dose prescribed in the first line, there is a risk of 5-FU underexposure.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an increase in endogenous compounds potentially leading to DPD inhibition could be observed in the plasma of patients with renal impairment. 20 , 22 , 23 , 24 Nevertheless, a case of dialyzed patients who tolerated standard 5-FU doses despite high levels uracilemia has been observed, 10 questioning the uracilemia-based phenotype in this situation. In the case of ‘false’ hyperuracilemia, as a pre-therapeutic plasma value of U ≥ 16 ng/ml may lead to a decrease in the 5-FU dose prescribed in the first line, there is a risk of 5-FU underexposure.…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits the formation of 5-FU catabolites that either may exert toxicity or may interfere with the antitumor activity of 5-FU. It is reported that more than 80% of 5-FU is converted to FBAL, a neurotoxic catabolite. The developed DPD inhibitor eniluracil has shown potent inhibitory activity with no significant neurotoxicity and cardiotoxicity. Thereby, this DPD inhibitor is a protective agent that may not only counter the 5-FU resistance but also reduce the toxicity induced by 5-FU. , In humans, neutropenia is the main side effect caused by eniluracil as observed with a 5-day schedule and diarrhea with a 28-day schedule .…”
Section: Strategies To Counter Dpd-mediated Resistance To 5-fumentioning
confidence: 99%
“…However, the use of 5-fluorouracil (5-FU) and its oral pro-drug, capecitabine, are associated with a significant risk of toxicity. This toxicity could be enhanced in patients with dihydropyrimidine dehydrogenase (DPD) deficiency 1 2. For this reason, on June 2020, the Spanish Agency for Medicines and Health Products recommended genotype and/or phenotype testing in patients who are candidates for these therapies 3…”
Section: Introductionmentioning
confidence: 99%